Using Project-Based Learning in Enhancing Students' Speaking Skill at SMA PSKD 7 - Kaunang, Chrisce Juonata (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
AbstractThe objectives of this research were to improve the students’ speaking skill and students’ interest about learning speaking by using Project-based learning. This research used classroom action research method in which the subject was the 25 ten graders of SMA PSKD 7 Depok and the subjects consisted thirteen males and twelve females. The quantitative data were analyzed by computing the students’ score of pre-test, post-test 1, and post-test2. Based on the data results, the mean score of pre-test, post-test in Cycle1, and post-test Cycle2 were respectively 49.12, 66.4, and 70.08. The gain of pre-test to post-test1 was 35.17%, the gain of post-test1in cycle 1 to post-test cycle 2 was 6.14%, and from the pre-test to post-test 2 in cycle 2 was 43.48%. The qualitative data were described based on interview and field-note to the improvement of students’ speaking skill. The findings showed that Project-based learning could improve the students’ speaking skill, it is suggested to use this method in teaching speaking skill. Keywords: CAR, Project-based learning